Faktor-Faktor Yang Mempengaruhi Revisit Intention Wisatawan Kawah Putih - Muhamad Syahrul Ramdani; Yadi Ernawadi (UNIVED Press, 2023)
This study is intended to examine the effect of visitor engagement on revisit intention which is mediated by the memorable tourism experience of tourists at the Kawah Putih tourist destination in Bandung Regency. The instruments used in this study have passed the construct validity test, advance validity test, concurrent validity test, and reliability test. The instrument was used as a data collection tool from respondents, namely domestic tourists with a minimum age of 17 years who already had experience visiting tourist destinations which were the objects assessed in this study as many as 100 people. The data collection technique used is cross-sectional or one shot study. The data analysis technique used is multiple linear regression using SPSS version 25 and using the Sobel test. The findings of this study indicate that enthusiasm and absorption partially affect revisit intention. Future research can propose other concepts that are thought to have a positive effect on revisit intention. The results of this study are also useful for the management of the object being assessed and similar tourism industries regarding the design of strategies that are relevant to improving the quality of these attributes.